2010
DOI: 10.4321/s1130-01082010000700003
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of endoscopic ultrasonography in preoperative gastric cancer staging: diagnostic yield and therapeutic impact

Abstract: Objectives: to evaluate the diagnostic yield of endoscopic ultrasonography in loco-regional staging of gastric cancer in our medium and to determine the impact of this technique on later therapeutic management.Material and methods: this is a retrospective study carried out on patients histologically diagnosed with gastric adenocarcinoma who had been referred for endoscopic ultrasonographic examination. The technique results were compared with those obtained from surgical samples and/or from exploratory laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Until now, most clinical studies that examined the accuracy of EUS were conducted exclusively on the specific part of depth of invasion or studies that analyzed the accuracy on T stages. (4,5,16,17) It could be anticipated that in our study, it was analyzed including all types of infiltration depth that could be classified, and thus lower concurrence rates were shown in comparison with past studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Until now, most clinical studies that examined the accuracy of EUS were conducted exclusively on the specific part of depth of invasion or studies that analyzed the accuracy on T stages. (4,5,16,17) It could be anticipated that in our study, it was analyzed including all types of infiltration depth that could be classified, and thus lower concurrence rates were shown in comparison with past studies.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, in the preoperative diagnosis of disease stage of gastric cancer, attentions have been focused on the accuracy and usefulness of EUS, and several studies have reported that EUS is useful for the diagnosis of local disease stage of gastric cancer. (2,4,5,16) EUS diagnoses the T stage of tumors depending on the depth of infiltration that destroys the normal layer structure of stomach wall by the low echo irregular mass findings. (17) Although it is different depending on the literature, for the diagnosis of the T stage of gastric cancer, the accuracy of EUS has been reported to be 65-92%, and it may be influenced by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most of the patients who were diagnosed for gastric cancer and sent to the clinic for surgery were in advanced stages so reliable staging devices such as endoscopic ultrasonography, which can demonstrate the depth of invasion, seem to be a good option before deciding lymphatic mapping and using SLN biopsy for planning the extension of lymphadenectomy. We used frozen section biopsies for evaluating SLN status intraoperatively and micrometastases were assessed using multiple sections and IHC in negative nodes.…”
Section: Discussionmentioning
confidence: 90%
“…The reliability of endoscopic ultrasound depends on the specialist who performs it (7). This test can have sensitivity for clinical T staging between 65-92% and for N stage between 50-95% and can result in a change in therapeutic management in approximately 25% of cases (8). CT (computed axial tomography) is used for the diagnosis of distant spread of the disease, with a sensitivity for clinical T staging between 43-82%.…”
Section: Surgical Treatmentmentioning
confidence: 99%